Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Given the following:
[tex]\begin{gathered} f(n+1)=f(n)-2 \\ \text{where f(1)=10} \end{gathered}[/tex]To generate the sequence, we have:
[tex]\begin{gathered} \text{when n=1} \\ f(1+1)=f(1)-2 \\ f(2)=10-2=8 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=2} \\ f(2+1)=f(2)-2 \\ f(3)=8-2=6 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=3} \\ f(3+1)=f(3)-2_{} \\ f(4)=6-2=4 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=4} \\ f(4+1)=f(4)-2 \\ f(5)=4-2=2 \end{gathered}[/tex]Hence, the correct option is Option D
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.